2016
DOI: 10.1038/srep28636
|View full text |Cite
|
Sign up to set email alerts
|

Mice that lack the C-terminal region of Reelin exhibit behavioral abnormalities related to neuropsychiatric disorders

Abstract: The secreted glycoprotein Reelin is believed to play critical roles in the pathogenesis of several neuropsychiatric disorders. The highly basic C-terminal region (CTR) of Reelin is necessary for efficient activation of its downstream signaling, and the brain structure of knock-in mice that lack the CTR (ΔC-KI mice) is impaired. Here, we performed a comprehensive behavioral test battery on ΔC-KI mice, in order to evaluate the effects of partial loss-of-function of Reelin on brain functions. The ΔC-KI mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 60 publications
1
36
1
Order By: Relevance
“…Third, the methylation pattern at the reelin gene promoter is different is ASD and control post-mortem brains [130]. Fourth, mice lacking the C-terminal region of reelin exhibit behavioral abnormalities related to ASD [131]; Fifth, the reeler ( rl −/− ) mouse, a spontaneously arising mutant mouse, displays several ASD-like morphological and behavioral traits [132, 133]. Sixth, cortical disorganization has been reported in reelin-deficient mice and in ASD patients [74, 134].…”
Section: Possible Mechanisms Of Developmental Neurotoxicity Of Traffimentioning
confidence: 99%
“…Third, the methylation pattern at the reelin gene promoter is different is ASD and control post-mortem brains [130]. Fourth, mice lacking the C-terminal region of reelin exhibit behavioral abnormalities related to ASD [131]; Fifth, the reeler ( rl −/− ) mouse, a spontaneously arising mutant mouse, displays several ASD-like morphological and behavioral traits [132, 133]. Sixth, cortical disorganization has been reported in reelin-deficient mice and in ASD patients [74, 134].…”
Section: Possible Mechanisms Of Developmental Neurotoxicity Of Traffimentioning
confidence: 99%
“…4H, white bars). This result was unexpected because a similar phenomenon was reported in the mice with attenuated Reelin signaling 14,37,38 but not in ADAMTS-3 KO mice 12 .…”
Section: Some Hippocampal Neurons Were Ectopically Located In Ki/ki Mmentioning
confidence: 62%
“…Mice with attenuated Reelin signaling often exhibit behavioral abnormalities 38,55 . It would be interesting to test if the PA-DV mutations could correct or improve these abnormalities.…”
Section: Second Bothmentioning
confidence: 99%
“…This mutant carries a short C-terminal deletion of RELN protein. Studies using multiple mutant mice have revealed that C-terminal region domain (CTR) is important for secretion, proteolytic cleavage, receptor binding, activation of downstream signaling, resulting in abnormalities in brain morphogenesis and behavior (D'Arcangelo et al, 1997;de Bergeyck et al, 1997;Nakano et al, 2007;Kohno et al, 2015;Nakamura et al, 2016;Sakai et al, 2016). Using genetic and biochemical analyses, we have demonstrated that the C-terminal deletion resulted in differential binding of RELN to its receptors; truncated RELN fails to bind to VLDLR but binds normally to APOER2 (Ha et al, 2017).…”
Section: Introductionmentioning
confidence: 89%